A LOCAL WISDOM-BASED INNOVATION MODEL IN THE DEVELOPMENT OF THE HALAL INDUSTRY IN MAKASSAR: AN EXPLORATORY STUDY OF MSMES - Reslawati, Reslawati (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This research aims to explore the innovation model based on local wisdom applied by Micro, Small, and Medium Enterprises (MSMEs) in the development of the halal industry in Makassar City. In the context of increasing global attention to the halal economy, this study offers an interdisciplinary approach that blends the perspectives of cultural anthropology, community economics, and religious studies. Qualitative methods were used through in-depth interviews, participatory observations, and document analysis on selected MSMEs in the culinary, fashion, and herbal products sectors. Preliminary results show that innovative practices are heavily influenced by local values such as siri' na pacce, community solidarity, and contextual religious interpretations. This study concludes that local wisdom is not only a source of business ethics but also a strategic framework in building sustainable halal competitiveness. These findings are expected to enrich the literature on the halal industry from a non-hegemonic perspective and contribute to regional economic development policies based on local values.